Investigation of neuron T cell interaction in central nervous system tuberculosis - Choshi, Phuti Sophia (Division of Chemical Pathology, 2017)
Tuberculosis of the central nervous system (CNS TB) is the severest form of tuberculosis. It is classified as extra-pulmonary tuberculosis due to dissemination of Mycobacterium tuberculosis (Mtb) bacilli from the lung to the brain. It affects mostly children and immune suppressed individuals and high incidents of death occur as a result of missed diagnosis and delayed treatment. Therefore, the is a need for improved therapeutic strategy and a better understanding of the CNS immunity; investigate cells targeted for infection, their respective response to infection and interaction with different cell types to the overall protection of the CNS - as accumulating evidence indicates a dynamic neuronal lymphocyte interplay that defines outcomes of diseases. A novel observation was previously made, that neurons are infected by Mtb during in vitro and in vivo infection. The aim of this study was to further characterize neural responses induced by mycobacteria using hippocampal primary neuron cultures, infected with H37RV and BCG. Secondly, this study investigated the importance of interaction between neurons and immune cells in immunity against mycobacterial challenge using an optimised neuron T cell co-culture model. Investigation included identifying the production levels of neuronal cell surface markers and cytokines induced by Mtb. In flowcytometry and ELISA analyses, infection exhibited a robust inflammatory response with increased neuronal production of cytokines such as IL1β, IL6, TNF and regulatory cytokine IL10 in vitro and in vivo. Neuronal MHC class I expression was upregulated by infection, suggesting possible antigen dependent interactions between neuron and CD8+ T cells. In co-cultures, neurons induced expression of Tbet, RorγT and Gata3 T cell transcription factors through direct contact with T cells. These data highlighted the likelihood of neurons activating T cells upon mycobacterial stimulations. It may potentially be utilised to broaden the understanding of CNS immunity under pathological conditions and possibly lead to identification of novel immunomodulatory targets that could be exploited for new rapid sensitive diagnostics and early opportune intervention against CNS TB – reducing morbidity and mortality associated with the disease.